Hydrogen bonding in meso-4,5-diphenyl-3,6-diazaoctane-1,8-diol: the formation of one-dimensional linear chains of edge-fused rings - Dinçer, M; Özdemir, N; Saydam, S; Bekaroglu, Ö; Büyükgüngör, O (Int Union Crystallography, 2006)
The molecule of the title compound, C18H24N2O2, resides on a crystallographic inversion centre. The molecule adopts a transoid conformation with respect to the central C - C single bond and is in the meso form. A polarimetric study of the compound did not show any optical activity, indicating that the compound is a racemic mixture entirely consistent with the centrosymmetric C2/c space group. In the molecule, there is one intramolecular N - H center dot center dot center dot O interaction, resulting in the formation of a five-membered ring. In the crystal structure, intermolecular O - H center dot center dot center dot N and C - H center dot center dot center dot O interactions are also observed. These interactions form an R-2(2)( 9) ring and one-dimensional linear chains of edge-fused rings running parallel to the [010] direction, which stabilize the crystal packing.
Keywords: Crystal-Structure; C-H...O